Population-Based Study of the Clinical Characteristics and Risk Factors of Ischemic Colitis - Wu, Xiaxia; Bao, Zhijun (Turkish Journal of Gastroenterology, 2021)
Background: Ischemic colitis (IC) is a common ischemic disorder of the colon caused by insufficient blood supply to the colonic mucosa.This study aimed to identify the clinical characteristics, comorbidities, and risk factors in patients with IC.Methods: We performed a retrospective population-based study using electron video-colonoscopy imaging and pathological biopsiesfrom 168 patients diagnosed with IC. A retrospective controlled study was used to analyze differences between a young to middle-agedpatient group (78 cases) and an elderly patient group (90 cases) on the basis of clinical characteristics and risk factors.Results: The primary symptoms in the 168 patients with IC were abdominal pain, diarrhea, and hematochezia. White blood cells (WBC),neutrophilic granulocyte percentage (NEUT%), C-reactive protein (CRP), and D-dimer were significantly elevated in elderly patients. Thesigmoid colon and descending colon were the most common lesion locations (57.1% and 33.9%, respectively). Hypertension, cerebralinfarction, and coronary heart disease were the most common comorbidities in elderly patients, while smoking history was the mostcommon risk factor in young to middle-aged patients.Conclusion: The sigmoid colon and descending colon are the most affected locations in IC. Hypertension, diabetes mellitus, and cerebralinfarction are the most common risk factors and comorbidities.